Postimperialni patriarhat in karnevaleskna periferija - Vidmar, Ksenija H. (Teorija in praksa, 2021)
This article studies perceptions of Melania Trump as The First Lady in the USA and in Slovenian public spaces. The analysis first investigates media depictions of Melania Trump in the weekly magazine The New Yorker. The main finding of the comparison is that representations in the USA focus on The First Lady's immigrant status and her roots in the former socialist East. Yet, in contrast, in Slovenia the fact of her ethnic origin is mobilised to create a national fantasy which aims to establish a distance from the socialist past. Still, reactions to the wooden statue of Melania in her hometown of Sevnica suggest a contested struggle over a post-socialist identity, in effect undermining the centre-periphery dichotomy. Based on these observations, the research question addresses the fate of symbolic motherhood in an era of the transnationalisation of modern societies.
Keywords: East; gender; media representations; medijske reprezentacije; nacionalizem; nationalism; post-socialism; postsocializem; Slovenia; Slovenija; spol; Trump, Melania; United States od America; Vzhod; Združene države Amerike